2010
DOI: 10.1098/rsif.2010.0125.focus
|View full text |Cite
|
Sign up to set email alerts
|

Surface-enhanced Raman scattering biomedical applications of plasmonic colloidal particles

Abstract: This review article presents a general view of the recent progress in the fast developing area of surface-enhanced Raman scattering spectroscopy as an analytical tool for the detection and identification of molecular species in very small concentrations, with a particular focus on potential applications in the biomedical area. We start with a brief overview of the relevant concepts related to the choice of plasmonic nanostructures for the design of suitable substrates, their implementation into more complex ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
177
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(182 citation statements)
references
References 151 publications
0
177
0
1
Order By: Relevance
“…For the sample obtained by adding 150 μL of AgNO 3 , the Raman intensity at 1619 cm −1 was 28 times higher than that for AuNR@mSiO 2 ( Figure S8, Supporting Information), which was attributed to the much greater Raman enhancing ability of Ag than Au. 37 The SERS signal variations could also be dynamically monitored during the Ag coating process. Figure 3d shows a typical set of SERS spectra collected at different time intervals in one reaction system containing 150 μL of AgNO 3 .…”
Section: Research Articlementioning
confidence: 99%
“…For the sample obtained by adding 150 μL of AgNO 3 , the Raman intensity at 1619 cm −1 was 28 times higher than that for AuNR@mSiO 2 ( Figure S8, Supporting Information), which was attributed to the much greater Raman enhancing ability of Ag than Au. 37 The SERS signal variations could also be dynamically monitored during the Ag coating process. Figure 3d shows a typical set of SERS spectra collected at different time intervals in one reaction system containing 150 μL of AgNO 3 .…”
Section: Research Articlementioning
confidence: 99%
“…In contrast to conventional methods stated earlier, higher detection limits in addition to a complete structural characterisation of the target molecule can be achieved with SERS [18] without the need for staining or expressing fluorogenic proteins. It has also been demonstrated that SERS can be applied to living cells in order to monitor cellular functions [19], cell response to stress [20] and apoptosis [21].…”
Section: Introductionmentioning
confidence: 97%
“…Thirdly, it remains very hard for us to quantify the SERS intensities as currently no tool or model is available to us for means of calculation [41]. The SERS intensities will depend several factors such as particle sizes, Raman cross section [42] and concentration of the AuNPs [43], which will make it too complex for us to control [44,45].…”
Section: Etching Rates and Diffusion Coefficients Of Cyanidementioning
confidence: 99%